The Impact of Healthy Leader and Organization Climate on Teacher Well-being: Self-Efficacy as an Intervening and Meaningful Work as a Moderating - Wahyudi Triwiyanto; Fathur Rokhman; Joko Sutarto; Tri Suminar (Universitas Negeri Semarang, 2023)
This study examines the effect of